2019
DOI: 10.32535/jicp.v2i1.443
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Performance Through Competitive Advantage Based on Innovation in Educational Service at Private Polytechnics in Indonesia

Abstract: Today, private polytechnics are required to innovate towards competitive advantage and superior performance in the higher education sector. However, in reality the accreditation is low, there is a lack of intellectual property rights and patents, many students drop out and have a long working period for graduates. Using a survey of all private polytechnics in West Java and Banten Province in Indonesia 30 institutions with 876 respondents from faculty members and students assigned randomly. The results of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…This study aims to address research gaps identified by Preda (2014) and Jurksiene and Pundziene (2016) by demonstrating the significant impact of AIN on SCA and INVPTES. This finding also supports Burhanudin et al (2019) with the same results with different research objects and locations.…”
Section: Discussionsupporting
confidence: 90%
“…This study aims to address research gaps identified by Preda (2014) and Jurksiene and Pundziene (2016) by demonstrating the significant impact of AIN on SCA and INVPTES. This finding also supports Burhanudin et al (2019) with the same results with different research objects and locations.…”
Section: Discussionsupporting
confidence: 90%